Evaluation of two embryo transfer protocols in Obispo ewes from the Montaña of Guerrero, Mexico - Resendiz-Aguilar, Omar; Martínez-Rojero, Rubén Darío; Mejía-Villanueva, Vicente Octavio; Hernández-Ignacio, Javier (Ecosistemas y Recursos Agropecuarios, 2022)
The objective was evaluated the response of Creole Obispo ewes a two Multiple Ovulation and Embryo Transfer (MOET) protocols. Eight donors received for 11 d intravaginal device with of Progesterone (0.3 g), and the ewes of the control group (n = 4) received 9.0 mL (180 mg) i.m. of FSH-P in decreased doses, vs 7.0 mL of FSH-P (140.0 mg) for the alternative treatment (n = 4, reduced dosage). Evaluations included superovulation response (75.0 vs 75.0%), number of luteal corpus (9.3 1.5 vs 11.3 0.9), collected embryos (7.0 1.2 vs 9.2 1.3) and transferable embryos (6.1 1.2 vs 8.7 1.8) for donor ewe, and fertility rate in the recipient females (62.5 vs 58.8%). Ji-Square and Exact Fisher tests and variance analysis were utilized. Differences were no significant (p > 0.01) and the Obispo ewes respond in the same way to both protocols.